Development of Learning Media Based on Arthropoda (Crustacea) Filum Diversity in Kampai Island of SD Negeri 050778 Langkat District, Sumatera Utara - Budianto, Budianto; Warsodirejo, Pandu Prabowo (International Journal for Educational and Vocational Studies, 2019)
This study aims to develop learning media that can be used by natural science teachers in SD Negeri 050778 by referring to RND-based media development methods (Research and Development) which will later use descriptive analysis methods and development methods. In making Blended Learning media where this media is in the form of learning videos using the Camtasia and Wondershare Quiz Creator application contains recorded video clips and questions about how to sample species, species diversity, and species collection techniques from Phylum Arthropods at SD Negeri 050778 Kampai Langkat Island, North Sumatra. The purpose of this research is descriptive analysis which is to obtain data on the diversity of the Artrhopoda Phylum from the Crustacean class which is very numerous and easily found around the coast of the island of Kampai. Crustacean diversity data obtained were analyzed using species abundance analysis method. Then the learning video development data will then be tested on students and science teachers as a test sample. From the field results found 8 dominant species of the Decapoda Order, including the Mangrove Crab (Scylla serrate), tiger shrimp (Panaeus monodon), Lobster Shrimp (Panulirus sp.), Ghost Crab (Ocypode kuhlii), Crab Uca Viola (Uca vocans) , Uca Petarung Crab (Uca annulipes), Centipede Shrimp (Squilla mantis), Klomang (Bernhardus Pagurus). From the three stations where Crustacea species sampling locations were obtained a diversity index of 0.85% at Station 1 with Species dominance, namely Centipede Shrimp, then 1.76% at Station II with Species dominance, namely Klomang (Pagurus bernhardus), and 0 , 43% with species dominance, namely Shrimp Prawn (Panaeus monodoni). From the analysis calculations of 30 students the results of a large group trial for development data are: (a) a group of 30 students an average of 97.85% (very decent), (2) Science Teacher Test Data of 87% (feasible category).